The search for the source : analysis of what drives the repetitive ICT outsourcing and insourcing ebb and flow phenomena in the South African ICT industry - Becker, Pieter Jacobus (My University, 2017)
The goal of this study has been to research two factors: What are the drivers for companies to outsource ICT services, and secondly what are the drivers for those companies to insource those services and then to understand whether there is indeed a trend to this phenomenon where companies continuously insource and outsource these services and if it does exist, the reasons for such a trend. The research was performed using analytical methods such as qualitative and quantitative research in the form of surveys, interviews, data collection and literature review to determine the underlying factors of this phenomenon in South Africa. The results of this research found that there are commonalities between the research that was conducted internationally and this research done in South Africa. The main drivers to outsource and insource services are mainly related to the pursuit of cost efficiencies and a company outsourced services moving closer to the business as the company’s strategies evolved. The results of this research have shown that there does indeed exist a trend where companies insource and outsource their services as the technology matures, the costs decrease and strategies changes where outsourced services are now critical to business value delivery. The trend to change strategies are typically related to the original contracting terms of between 3-7 years, but the main driver for the trends related to how quickly a technology matured so that it could be delivered cheaper and faster internally to the company. The main highlight of the research can be found in chapter 6.6 “The Search for the Source Model” where the evolution of outsourcing and insourcing is described and the future of outsourcing predicted based on the research conducted. The results indicated that insourcing and outsourcing as we know it will evolve into something new. The new model will have multi-sourcing at its core where many suppliers each deliver their unique service to the same customer together with many other suppliers. This will result in customers needing to become more competent in managing multi-vendor relationships and service. Expertise as a Service (ExaaS) is likely to become the next nice where outsourcers need to operate to continue to add value to customers. The current outsourcing market has become saturated with competitors, low margins and many commoditised products. As customer’s strategies evolve to embrace new innovations and technologies so too does the outsourcing models need to evolve beyond providing commoditised services, as a service. Outsourcing companies should rather move into the higher cognitive value - 3 - chain that focuses on adding business value to the end user throughout the business value chain and up and down the information technology stack to remain relevant. Keywords: Outsourcing, Insourcing, Information technology, Information communication technology, South Africa, Expertise as a Service, Outsourcing trends.
MBA
Keywords: Electronics data processing departments -- South Africa -- Contracting out. Contracting out -- South Africa. Information technology -- South Africa.